Alexithymia and professional quality of life in radiation oncology: The moderator effect of the professional profile. (May 2021) - Franco, Pierfrancesco; Di Tella, Marialaura; Tesio, Valentina; Gasnier, Anne; Petit, Steven; Spalek, Mateusz; Bibault, Jean-Emmanuel; Dubois, Ludwig; Mullaney, Laura; Redalen, Kathrine Røe; Chargari, Cyrus; Perryck, Sophie; et al.
Highlights: Professional quality of life is crucial for radiation oncology professionals. Alexithymia increases compassion fatigue and decreases compassion satisfaction. Professional category impacts well-being at work. Professional profile has a moderator role on secondary traumatic stress. Teaching emotional awareness should be fostered. Abstract: Background and purpose: Cancer care can be taxing. Alexithymia, a personality construct characterized by difficulties in identifying and describing feeling and emotions, an externally-oriented thinking style and scarcity of imagination and fantasy, is significantly correlated with higher levels of both secondary traumatic stress (STS) and burnout and lower levels of compassion satisfaction in medical professionals in radiation oncology. In this study, we aimed to assess the difference in professional quality of life (QoL) and the association with alexithymia in this multidisciplinary field depending on the specific profession (radiation/clinical oncologist, RO; medical physicist, MP; radiation therapist, RTT). Material and methods: The study was conducted via an online questionnaire, receiving 1500 submissions between May and October 2018. Alexithymia was assessed via the Toronto Alexithymia Scale (TAS-20) and professional QoL was evaluated using the Professional Quality of Life Scale (ProQoL) version 5. Comparisons between the RO, RTT, and MP groups were performed by ANOVA or MANOVA, followed by Bonferroni corrected ANOVAs for continuous variables, and Pearson's chi-square test for categorical variables. The effect size was determined by calculating partial eta-squared (η 2 ). Results: Profession had a moderator role on the correlation between alexithymia and STS, with RO being at a higher risk than MP and RTT. Further, the results of this study demonstrate the relevant point prevalence of decreased well-being at work even for professional categories such as MP despite the more technical profile and reduced interaction with patients. Conclusions: This study demonstrates the importance of alexithymia as a factor contributing to decreased professional QoL amongst radiation oncology professionals. Alexithymic ROs are impacted to a higher extent compared to MPs and RTTs by the indirect exposure to patients suffering. It is worth addressing these observations in professional education, aiming to improve QoL for healthcare personnel.